2006
DOI: 10.1007/s00247-006-0144-z
|View full text |Cite
|
Sign up to set email alerts
|

Mastoid fontanelle approach for sonographic imaging of the neonatal brain

Abstract: This pictorial review describes in detail the examination technique used to study the neonatal brain via the mastoid fontanelle and offers a panoramic view of the anatomical structures that can be identified in each US slice. The brain lesions are grouped as congenital malformations, haemorrhage, cerebellar lesions and sinus venous thrombosis. In each section, the additional information obtained through the mastoid fontanelle is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 20 publications
0
34
0
1
Order By: Relevance
“…At least two slices should be performed, depicting the cerebral peduncles, the vermis, the cerebellar hemispheres, the fourth ventricle, the quadrigeminal plate and the cisterna magna [20]. The posterior fontanelle may be used to better visualize the occipital lobes and occipital horns and to distinguish between a prominent choroid plexus and a small intraventricular haemorrhage [1].…”
Section: How Do We Perform Us?mentioning
confidence: 99%
“…At least two slices should be performed, depicting the cerebral peduncles, the vermis, the cerebellar hemispheres, the fourth ventricle, the quadrigeminal plate and the cisterna magna [20]. The posterior fontanelle may be used to better visualize the occipital lobes and occipital horns and to distinguish between a prominent choroid plexus and a small intraventricular haemorrhage [1].…”
Section: How Do We Perform Us?mentioning
confidence: 99%
“…Examples of these supplemental acoustic windows are the lambdoid (posterior), mastoid and lateral (temporal) fontanels. So far, however, only few NICUs use these additional acoustic windows routinely [2][3][4][5] . Doppler techniques can be used for screening patency of intracranial vessels.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the echogenic tentorium and vermis may impede visualization. The mastoid fontanelle (MF) enables a better view of the PF [10][11][12]. A previous study [13] demonstrated that addition of MF views in preterm infants improved detection of cerebellar injury as compared to CUS with only AF views.…”
Section: Introductionmentioning
confidence: 99%